Global justice networks : geographies of transnational solidarity - Routledge, Paul, 1956- (Perspectives on democratic practice., 2009)
This book provides a critical investigation of what has been termed the?global justice movement?. Through a detailed study of a grassroots peasants? network in Asia (People?s Global Action), an international trade union network (the International Federation of Chemical, Energy, Mining and General Workers) and the Social Forum process, it analyses some of the global justice movement?s component parts, operational networks and their respective dynamics, strategies and practices. The authors argue that the emergence of new globally-connected forms of collective action against neoliberal globalis.